An Efficient Synthesis of Darunavir Substantially Free from Impurities: Synthesis and Characterization of Novel Impurities. Issue 14 (15th April 2019) - Rapolu, Rajesh Kumar; Areveli, Srinivas; Raju, V. V. N. K. V. Prasada; Navuluri, Srinivasu; Chavali, Murthy; Mulakayala, Naveen
Abstract: An improved and novel process for the synthesis of antiviral drug Darunavir using 4‐(1, 3‐dioxoisoindolin‐2‐yl)benzene‐1‐sulphonyl chloride was described to eliminate the critical furan dimer impurity which will be formed during the process. The best reaction conditions were identified by evaluating the impurity profile and their formation during the synthesis. The optimization of the process was made to control the furan dimer impurity which was one of the critical parameters in the synthesis of darunavir. All the impurities formed during the synthesis were identified, synthesized and characterized. Abstract : An improved and novel process for the synthesis of antiviral drug Darunavir using 4‐(1, 3‐dioxoisoindolin‐2‐yl)benzene‐1‐sulphonyl chloride was described to eliminate the critical dimer impurity which will be formed during the process. The best reaction conditions were identified by evaluating the impurity profile and their formation during the synthesis. The optimization of the process was made to control the dimer impurity which was one of the critical parameters in the synthesis of darunavir. All the impurities formed during the synthesis were identified, synthesized and characterized.